Effect of core resistance training on gait performance of patients with knee osteoarthritis (OA): a preliminary study - Liau, S.N.; Malehah Mohd Noh; Khin, Nyein Yin; D. Maryama Ag. Daud (Faculty of Science & Natural Resources, UMS, 2022)
This study is to evaluate the effects of core resistance training on gait performance in knee osteoarthritis (OA) patients, methodology part included the 6 subjects were randomly assigned evenly into experimental group (EG) and control group (CG). The treatment group received 10 weeks of core training intervention (3 times per week) and being analysed for their gait performance fortnightly (week 1, week 4, week 7 and week 10) whereas the control group was only being assessed with the gait performance fortnightly. For gait performance, we calculated the velocity (km/h), cadence (step/time), step and stride lengths (cm), and step time (sec). The present result depicted there was a significantly difference in the gait performance during the post-training intervention compared to the pre-training intervention. We concluded that core resistance training is a beneficial complementary choice for knee OA patients in enhancing their walking gait patterns.